Asymmetry of planum temporale constrains interhemispheric language plasticity in children with focal epilepsy - Pahs, Gerald (Oxford University Press, 2013)
Reorganization of eloquent cortex enables rescue of language functions in patients who sustain brain injury. Individuals with left-sided, early-onset focal epilepsy often show atypical (i.e. bilateral or right-sided) language dominance. Surprisingly, many patients fail to show such interhemispheric shift of language despite having major epileptogenic lesions in close proximity to eloquent cortex. Although a number of epilepsy-related factors may promote interhemispheric plasticity, it has remained unexplored if neuroanatomical asymmetries linked to human language dominance modify the likelihood of atypical lateralization. Here we examined the asymmetry of the planum temporale, one of the most striking asymmetries in the human brain, in relation to language lateralization in children with left-sided focal epilepsy. Language functional magnetic resonance imaging was performed in 51 children with focal epilepsy and left-sided lesions and 36 healthy control subjects. We examined the association of language laterality with a range of potential clinical predictors and the asymmetry of the length of the planum temporale. Using voxel-based methods, we sought to determine the effect of lesion location (in the affected left hemisphere) and grey matter density (in the unaffected right hemisphere) on language laterality. Atypical language lateralization was observed in 19 patients (38%) and in four controls (11%). Language laterality was increasingly right-sided in patients who showed atypical handedness, a left perisylvian ictal electroencephalographic focus, and a lesion in left anterior superior temporal or inferior frontal regions. Most striking was the relationship between rightward asymmetry of the planum temporale and atypical language (R = 0.70, P < 0.0001); patients with a longer planum temporale in the right (unaffected) hemisphere were more likely to have atypical language dominance. Voxel-based regression analysis confirmed that increased grey matter density in the right temporo-parietal junction was correlated with right hemisphere lateralization of language. The length of the planum temporale in the right hemisphere was the main predictor of language lateralization in the epilepsy group, accounting for 48% of variance, with handedness accounting for only a further 5%. There was no correlation between language lateralization and planum temporale asymmetry in the control group. We conclude that asymmetry of the planum temporale may be unrelated to language lateralization in healthy individuals, but the size of the right, contra-lesional planum temporale region may reflect a ‘reserve capacity’ for interhemispheric language reorganization in the presence of a seizure focus and lesions within left perisylvian regions.